2019
DOI: 10.1002/wnan.1586
|View full text |Cite
|
Sign up to set email alerts
|

Inhalable nanotherapeutics to improve treatment efficacy for common lung diseases

Abstract: Respiratory illnesses are prevalent around the world, and inhalation‐based therapies provide an attractive, noninvasive means of directly delivering therapeutic agents to their site of action to improve treatment efficacy and limit adverse systemic side effects. Recent trends in medicine and nanoscience have prompted the development of inhalable nanomedicines to further enhance effectiveness, patient compliance, and quality of life for people suffering from lung cancer, chronic pulmonary diseases, and tubercul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 199 publications
1
61
0
3
Order By: Relevance
“…Despite the nonnegligible safety concerns caused by their low systemic toxicities, this method remains a promising approach to target lung cancer cells during the targeted therapy process [178]. It has been indicated that nanomedicine inhalation can also be used to treat lung cancer [179]. One study found that siRNA combined with PTX inhalation via nanostructured lipid carriers can significantly decrease lung tumor volumes [180].…”
Section: Resultsmentioning
confidence: 99%
“…Despite the nonnegligible safety concerns caused by their low systemic toxicities, this method remains a promising approach to target lung cancer cells during the targeted therapy process [178]. It has been indicated that nanomedicine inhalation can also be used to treat lung cancer [179]. One study found that siRNA combined with PTX inhalation via nanostructured lipid carriers can significantly decrease lung tumor volumes [180].…”
Section: Resultsmentioning
confidence: 99%
“…Once reaching the alveolar region, microparticles are expected to readily dissolve, delivering the nanocarriers which, in turn, are internalized by AMs and can release the encapsulated drug. [40,51,77,78] Some recent approaches applying passively targeted nanocar-riers for pulmonary administration route are summarized in Table 2.…”
Section: Passive Targetingmentioning
confidence: 99%
“…They can thus also restrict drug exposure to healthy cells. However, they were also associated with certain loopholes such as bolus drug release culminating into severe lung toxicity, short residence time, and poor aqueous solubility [10]. The other contemporary TB treatment includes oral and parenteral dosage forms.…”
Section: Nanotechnological Approach For Combating Tbmentioning
confidence: 99%